A CD300c-Fc Fusion Protein Inhibits T Cell Immunity - Cui, Cheng; Su, Min; Lin, Yujun; Lai, Laijun (Frontiers in Immunology, 2018)
T cell responses are fine-tuned by co-stimulatory and co-inhibitory molecules. Among the T cell regulators, the B7 family members are of central importance. The recent success in targeting the B7 family molecules for the treatment of immune-related diseases has attracted intense interest in identifying additional B7-related molecules. In this study, we describe CD300c as a novel T cell co-inhibitory molecule that shares significant sequence homology with existing B7 family members. CD300c protein is expressed on professional antigen-presenting cells (APC), including B cells, monocytes, macrophages and dendritic cells (DCs). The putative CD300c counter-receptor is expressed on CD4 and CD8 T cells, and the expression levels are upregulated upon activation. Soluble human and mouse CD300c-Fc fusion proteins significantly inhibit the proliferation, activation, and cytokine production by CD4 and CD8 T cells in vitro. Administration of CD300c-Fc protein attenuates graft-versus-host disease (GVHD) in mice. Our results suggest that therapeutic interaction with the CD300c inhibitory pathway may represent a new strategy to modulate T cell-mediated immunity for the treatment of GVHD and autoimmune disease.